Numerical simulation of supercritical flow in open channel - Ng, Boon Chong (2006)
The presence of disturbances such as bends, contraction, expansion, junction, bridge piers in a drainage system is very common in Malaysia. These hydraulic structures often cause the channel flow to choke and form standing waves. The challenges for this numerical model lie in representing supercritical transition and capturing shocks. For this purpose, an unstructured two-dimensional finite-element model is used to solve the governing shallow water equations. This numerical model utilizes a characteristic based Petrov-Galerkin method implemented with shockdetection mechanism. The model testing demonstrates the ability of this numerical model to reproduce the speed and height of flow with the presence of hydraulic structure under different flow conditions. Four experiments, which consist of weir, contraction and 90Â° expansion, hydraulic jump and bridge pier, were conducted in laboratory Universiti Teknologi Malaysia (UTM). The Reynolds number for these experiments is within the range of 30000 to 47000. The numerical model results are compared quantitatively with experimental results, published numerical simulation and analytical solution. In general, the energy in the model is dissipated too fast and the short wave in the model tends to travel faster. The present model is not suitable for any surface flow that has steep gradients. Overall results show that the numerical model satisfactorily computed the water-surface profiles of the experiments data and exact solutions. The results demonstrate that the numerical model provides an alternative tool in validating theoretical finding and evaluating flow performance